Intrinsic MRI contrast from amino acid-based paramagnetic ionic liquids. Issue 6 (25th August 2020) - Gehlot, Praveen Singh; Gupta, Hariom; Rathore, Mangal Singh; Khatri, Kusum; Kumar, Arvind
Abstract : Paramagnetic ionic liquids (PMILs) comprising of natural amino acids and tetrachloroferrate(iii ) as constituent ions were prepared that act as highly efficient dual mode ( T 1 and T 2 ) responsive contrast agents for magnetic resonance imaging (MRI). Abstract : Paramagnetic ionic liquids (PMILs) comprising of natural amino acids and tetrachloroferrate(iii ) as constituent ions were prepared that act as highly efficient dual mode ( T 1 and T 2 ) responsive contrast agents for magnetic resonance imaging (MRI). The PMILs were characterized by ultraviolet-visible (UV), Raman and EPR spectroscopies, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and inductively couple plasma mass spectrometry (ICP MS). DNA stability in the presence of the PMILs was investigated using fluorescence spectrophotometry, circular dichroism (CD), zeta potential analysis, and gel electrophoresis. The behavior of synthesized PMILs as contrast agents was determined and compared with commercially available contrast agents using the rate of relaxivity. The PMILs synthesized herein are environmentally friendly, biodegradable, cost effective, easy to synthesize, stable at cell physiological pH (7.4), non-hazardous to animal DNA, and hence hold promise for future clinical use.